Morphological characteristics of cerebellum, pons and thalamus in Reccurent isolated sleep paralysis – A pilot study - Miletínová, Eva; Kliková, Monika; Dostalíková, Amálie; Bušková, Jitka (Frontiers in Neuroanatomy, 2024)
Introduction: Recurrent isolated sleep paralysis (RISP) is a rapid eye movement sleep (REM) parasomnia, characterized by the loss of voluntary movements upon sleep onset and/or awakening with preserved consciousness. Evidence suggests microstructural changes of sleep in RISP, although the mechanism of this difference has not been clarified yet. Our research aims to identify potential morphological changes in the brain that can reflect these regulations. Materials and Methods: We recruited 10 participants with RISP (8 women; mean age 24.7 years; SD 2.4) and 10 healthy control subjects (w/o RISP; 3 women; mean age 26.3 years; SD 3.7). They underwent video-polysomnography (vPSG) and sleep macrostructure was analyzed. After that participants underwent magnetic resonance imaging (MRI) of the brain. We focused on 2-dimensional measurements of cerebellum, pons and thalamus. Statistical analysis was done in SPSS program. After analysis for normality we performed Mann-Whitney U test to compare our data. Results: We did not find any statistically significant difference in sleep macrostructure between patients with and w/o RISP. No evidence of other sleep disturbances was found. 2-dimensional MRI measurements revealed statistically significant increase in cerebellar vermis height (p=0.044) and antero-posterior diameter of midbrain-pons junction (p=0.018) in RISP compared to w/o RISP. Discussion: Our results suggest increase in size of cerebellum and midbrain-pons junction in RISP. This enlargement could be a sign of an over-compensatory mechanism to otherwise dysfunctional regulatory pathways. Further research should be done to measure these differences in time and with closer respect to the frequency of RISP episodes.